Magnetic on-time transient electromagnetic method (MoTEM) for imaging magnetic susceptibility. Issue 3 (20th October 2022) - Melo, Aline; Li, Yaoguo
SUMMARY: We present the magnetic on-time transient electromagnetic (MoTEM) method for obtaining information about subsurface magnetic susceptibility from transient electromagnetic (TEM) measurements. The method uses the primary field produced by a TEM system as the inducing magnetic field and extracts from the measured late on-time response the magnetic responses produced by the subsurface magnetic susceptibility. The method assumes that the transmitter waveform is long enough to allow for the dissipation of eddy currents until the electric conductivity effect becomes negligible towards the end of the on-time transmission and that the measured magnetic field or its time derivative is dominantly the response to magnetic susceptibility. Using numerical simulations, we study the dissipation of the field produced by the conductivity anomaly for different times of the transmitter waveform and demonstrate that the signal becomes dominated by the susceptibility anomaly (MoTEM signal) at late on-time for both moving and fixed-loop sources. We present observational evidence for the presence of MoTEM responses by showing that they can be identified in field data measured from a fixed-loop ground TEM survey over the ultramafic units in the Raglan nickel belt. Our study lays the foundation for the MoTEM method, demonstrates that it can be realized with existing TEM acquisition systems, and provides the guidance for new system development. The MoTEM response could enable the mapping and imaging of subsurface susceptibility from the airborne EM data and, therefore, has the potential to double the information content in such data by imaging both conductivity and magnetic susceptibility.